Combined therapy with cisapride and cimetidine in severe reflux oesophagitis: a double blind controlled trial. Issue 5 (May 1988) - Galmiche, J P; Brandstätter, G; Evreux, M; Hentschel, E; Kerstan, E; Kratochvil, P; Reichel, W; Schütze, K; Soule, J C; Vitaux, J
Abstract : Combined treatment with cimetidine 1 g daily and cisapride 40 mg daily in patients with endoscopically diagnosed severe reflux oesophagitis was compared with single drug therapy (cimetidine and placebo). At the end of the six to 12 weeks treatment, 11 (46%) of the 24 patients under single drug therapy were endoscopically healed and three were improved. In contrast, 16 (70%) of the 23 patients under combined therapy were healed and all of the remainder were improved (p = 0.025). The severity of diurnal and nocturnal heartburn, decreased significantly more (p less than 0.05) on cimetidine + cisapride than on cimetidine + placebo. The combined treatment was well tolerated. These results suggest that combined therapy with cisapride and cimetidine may be useful in patients with severe reflux oesophagitis.